Rocket plants in response to nitrogen concentration in nutrient solution - Silva, Paulo Henrique S. [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Reis, Isaias Dos S. [UNESP]; Nascimento, Carolina S. [UNESP]; Nascimento, Camila S. [UNESP] (FapUNIFESP (SciELO), 2021)
Nitrogen (N) is the second most accumulated nutrient in rocket. This nutrient greatly affects growth, productivity and quality of the vegetable. Rocket is the second most widely grown leafy vegetable in hydroponic system; however, no studies on how N concentration in nutrient solution affects this crop can be found in literature. We studied four concentrations (79.2; 118.8; 158.4 and 237.6 mg L-1 of N) in a randomized block design with five replicates. Maximum number of leaves, leaf area, dry mass and productivity of rocket cv. ‘Folha larga’ were obtained with the highest N concentration. The rocket quality, evaluated by the nitrate content, was maximum with 210.2 mg L-1 of N and its value in the concentration which maximized productivity is in the acceptable range for vegetables; so, it is recommended to grow rocket with 237.6 mg L-1 of N in the nutrient solution.
Resposta da rúcula à concentração de nitrogênio na solução nutritiva
Keywords: Eruca sativa; Hydroponics; Leafy vegetables; Nitrate; Soil-free cultivation